2020
DOI: 10.3390/antiox9100912
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Treated Zizania latifolia Ethanol Extract Protects from UVA Irradiation-Induced Wrinkle Formation via Inhibition of Lysosome Exocytosis and Reactive Oxygen Species Generation

Abstract: Ultraviolet A (UVA) is a risk factor for photoaging and wrinkle formation. Zizania latifolia is an herbaceous perennial plant. It contains many bioactive compounds such as tricin that show antioxidative and anti-inflammatory effects. The aim of this study was to investigate the antiwrinkle effect of a mixture of hydrolytic enzyme (cellulase, hemicellulase and pectinase)-treated Z. latifolia extract (ZLE) and tricin on UVA-irradiated human dermal fibroblasts (HDFs) and SKH-1 hairless mice. Treatment of UVA-irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…[25][26][27][28] These experiments have demonstrated tricin to be protective against skin damage caused by UVA radiation and UVBmediated photoaging. [26][27][28] Another study found tricin to inhibit IgEmediated allergic reactions. 25 Although the literature on biological activities of tricin in conjunction with momilactones is limited, research suggests that momilactones A and B and tricin isolated from rice husk all exhibit antiaging effects.…”
Section: Tricinmentioning
confidence: 99%
See 2 more Smart Citations
“…[25][26][27][28] These experiments have demonstrated tricin to be protective against skin damage caused by UVA radiation and UVBmediated photoaging. [26][27][28] Another study found tricin to inhibit IgEmediated allergic reactions. 25 Although the literature on biological activities of tricin in conjunction with momilactones is limited, research suggests that momilactones A and B and tricin isolated from rice husk all exhibit antiaging effects.…”
Section: Tricinmentioning
confidence: 99%
“…Numerous studies have investigated tricin extracted from enzyme‐treated Zizania latifolia , a wild rice 25–28 . These experiments have demonstrated tricin to be protective against skin damage caused by UVA radiation and UVB‐mediated photoaging 26–28 . Another study found tricin to inhibit IgE‐mediated allergic reactions 25 .…”
Section: Components Of Rice and Dermatological Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…[61] The flavonoid tricin (116) was shown to improve the cutaneous system by regulating anti-inflammatory signaling pathways. [62] In addition, taxifolin (125) showed a good anti-inflammatory effect and could inhibited HT22 cells apoptosis at concentration of 2.5 μm (83% cell survival). [63] Flavonoids…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…The WBS is usually regarded as an ancient herbal medicine according to the Chinese ancient medicine literature. Previous studies have demonstrated that WBS exhibits antioxidant and antiultraviolet activities (An et al, 2020;Wang et al, 2017). According to the Chinese ancient medicine literature, "Compendium of Materia Medica" has alcoholismremission and hepatoprotective effects (Li, 2003).…”
Section: Introductionmentioning
confidence: 99%